Lingam as a symbolic representation of Lord Shiva - Mumbai Archive Project Team (Jio Institute, 2024)
The lingam is a symbolic representation of Lord Shiva, who is regarded as formless. Devotees believe that the mukhalingam, with its anthropomorphic mukha, makes the divine more accessible, allowing a deeper personal connection. The anthropomorphic face allows worshippers to engage in darshan, enhancing their devotional experience.